2021
DOI: 10.3389/feart.2021.747429
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on Water Availability in Water Source Areas of the South-to-North Water Diversion Project in China

Abstract: The South-to-North Water Diversion project (SNWD project) is a mega water project designed to help solve water shortages in North China. The project’s management and operation are highly influenced by runoff change induced by climate change in the water source areas. It is important to understand water availability from the source areas in the context of global warming to optimize the project’s regulation. Based on the projections of nine GCMs, the future runoff in the water source areas of the three diversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Previous studies reported that streamflow in upper Yangtze River presented an increasing trend [25] and that of the Yellow River basin no doubt showed a decreasing trend in all parts, mainly because of climate change and the large amount of human activities such as water intake in upstream and downstream, respectively [26][27][28][29][30]. At the same time, the results concluded by Liu [15] and Qiao [31] showed that the streamflow in Danjiangkou reservoir have decreased since the 1980s, and climate change contributed more than 80% of the change, mainly due to mainly the decrease in precipitation. The water diversion of the middle route is about ten times than that of the eastern route.…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies reported that streamflow in upper Yangtze River presented an increasing trend [25] and that of the Yellow River basin no doubt showed a decreasing trend in all parts, mainly because of climate change and the large amount of human activities such as water intake in upstream and downstream, respectively [26][27][28][29][30]. At the same time, the results concluded by Liu [15] and Qiao [31] showed that the streamflow in Danjiangkou reservoir have decreased since the 1980s, and climate change contributed more than 80% of the change, mainly due to mainly the decrease in precipitation. The water diversion of the middle route is about ten times than that of the eastern route.…”
Section: Introductionmentioning
confidence: 94%
“…where TWDi is the TWD for the ith year in (cubic meters/year) POPi is the population for the ith year in (capita) Scholars adopted various models to characterize the effect of climate change on water resources availability. Such models include (i) Water Balance Model developed by the Research Center for Climate Change (RCCC-WBM) [35], (ii) Hydrologiska Byrans Vattenbalansavdelning model (HBV) [36], (iii) Soil and Water Assessment Tool (SWAT) [37], and (iv) Soil-Vegetation-Atmosphere Model (SVAT) [9]. According to [38], the SVAT has the Scholars adopted various models to characterize the effect of climate change on water resources availability.…”
Section: Assessment Of the Domestic Water Scarcitymentioning
confidence: 99%
“…According to [38], the SVAT has the Scholars adopted various models to characterize the effect of climate change on water resources availability. Such models include (i) Water Balance Model developed by the Research Center for Climate Change (RCCC-WBM) [35], (ii) Hydrologiska Byrans Vattenbalansavdelning model (HBV) [36], (iii) Soil and Water Assessment Tool (SWAT) [37], and (iv) Soil-Vegetation-Atmosphere Model (SVAT) [9]. According to [38], the SVAT has the following strengths compared to the other models: (i) consideration of fine timestep analysis that goes in line with the time steps of the physical processes simulations, (ii) flexibility of the input parameters and their time-steps records, and (iii) consideration of the under-ground layer (e.g., soil layer), on-ground layer (e.g., vegetation layer), and over-ground layer (atmospheric layer) [38].…”
Section: Assessment Of the Domestic Water Scarcitymentioning
confidence: 99%
“…This number is predicted to increase to 14.8 km 3 /year by 2030. This waterway may soon play the same role it had in the past, simultaneously transporting scarce water resources to the arid northern regions [12,13]. In contrast, the focus of this discussion in this article-the Central Route project completed in 2014-is a new construction project.…”
Section: Introductionmentioning
confidence: 98%